Investigation of teacher candidates’ skills for preparing therefutational text of biodiversity - MERTOĞLU, HATİCE; ŞAHİN, FATMA (My University, 2022)
The aim of this study is to investigate the science teacher candidates’ ability to prepare misconceptions’ refutational text (RT). Thirty-five students from the third year of Marmara University Science Teacher Education participated in the study. The type of research method is qualitative, and the pattern is case study. The data collection tools of the research are interview forms about preparing misconceptions’ RTs prepared by pre-service teachers and preparing RTs by pre-service teachers. The researchers examined the science teacher candidates’ ability to prepare misconceptions’ RTs. Lack of knowledge about the misconceptions given to the teacher candidates and the lack of knowledge on the subject content of the given misconception are among the short comings. In order to develop misconceptions’ RTs by prospective teachers, the nature and importance of biology, chemistry, physics and laboratory courses given in the undergraduate level should be indicated to the prospective teachers.
Keywords: Biodiversity; science courses; misconception; refutational text; science teacher